Capability versus efficiency: contracting out park and road services in Norway. Issue 5 (11th July 2016) - Leiren, Merethe Dotterud; Lindholst, Andrej Christian; Solfjeld, Ingjerd; Randrup, Thomas Barfoed
Abstract : Purpose: – The purpose of this paper is to provide insights into the extent of, rationales for and outcomes of contracting out in the local road and park sectors in Norway. For understanding the use of contracting out in local governments, it highlights the relevance of the capability perspective in organisational literature as an alternative to the standard efficiency perspective. Design/methodology/approach: – The paper draws on four expert interviews and survey data gathered from park and road managers in Norwegian municipalities in 2015. Findings: – The study suggests that Norwegian municipalities primarily contract out park and road maintenance services when they do not have the capability to perform these services themselves. Cost concerns are also highlighted but of less importance. Moreover, lack of competition renders the use of contracting out as a potentially costly and less satisfying arrangement for organising service delivery. Research limitations/implications: – While the scope is limited to one country, Norway, future research may benefit from the theoretical perspectives, which have been used. Practical implications: – Policy guidelines should support a flexible use of various arrangements for service provision. Originality/value: – The dominating view among proponents of marketisation in the public sector suggests that contracting out to private contractors is undertaken to enhance economic efficiency compared to keeping service production in-house. This study suggests that this is not always the case – even in "most likely" sectors such as park and road maintenance.